Pengaruh Waktu Kontak terhadap Daya Adsorpsi Karbon Aktif pada Proses Purifikasi CH4 dari Biogas - Nani Harihastuti; Silvy Djayanti; Rame (Balai Besar Standardisasi dan Pelayanan Jasa Pencegahan Pencemaran Industri, 2016)
Direct utilization of biogas as a fuel often cause problems, i.e bad odor, metal corrosive, wall erosion and frequent fire extinguished. This is due to the presence of gas impurities in biogas such as H2S, NH3, CO2, H2, CO and water vapor (H2O), which will lower the value of calories from biogas and detrimental to the environment and health. The purpose of this research is to eliminate impurities gases, through a process called gas purification, until higher heat value of biogas is achieved. The methods were undertaken by adsorption process using activated carbon adsorbent with variable time contacts, to obtain the optimum adsorption power of activated carbon toward gas impurities that are present in wastewater. The results showed that removal/reduction of H2S of 99.99% was obtained from 4200 ppm to 0.22 ppm, NH3 removal reached 12.7%, from 94.96 ppm to 0.65 ppm, CO2 removal reached 77.48%, from 30,77% to 6.93%, water vapour (H2O) removal reached 97.95%, from 0.584 mg/L to 0.012 mg/L, which increased methane concentration (CH4) from 38.2% to 84.12%. This methane purification technology is renewable energy sources that is safe and environmentally friendly and also can be developed in other industries i.e tofu industries. The saturation of activated carbon adsorbents obtained after 48 hours. Adsorption of each impurities gas components by activated carbon are written as follows: 10.98 mg H2S/gram activated carbon/minute, 0.016 mg NH3/gram of activated carbon/minute, 0.090 CO2/gram activated carbon/minute.